The importance of migration for Caribbean development - Conway, Dennis (2000)
Assesses some of the challenges faced by the island micro-states of the Caribbean in the current world of macro-structural changes. Identifies some potential progressive 'development' avenues which hold promise for the future. Suggests that there are several ways migration and its consequences are likely to contribute to a sustainable future for Caribbean people and places.